![image](https://tex.z-dn.net/?f=%5Csqrt%7B3x-2%7D%3Ex-2)
x-2" alt="\sqrt{3x-2}>x-2" align="absmiddle" class="latex-formula">
Совокупность систем:
![image](https://tex.z-dn.net/?f=+%5Cleft+%5C%7B+%7B%7Bx-2%3C0%7D+%5Catop+%7B3x-2%5Cgeq+0%7D%7D+%5Cright.%5C%5C+%5Cleft+%5C%7B+%7B%7Bx-2%5Cgeq0%7D+%5Catop+%7B3x-2%3E%28x-2%29%5E2%7D%7D+%5Cright.+)
(x-2)^2}} \right. " alt=" \left \{ {{x-2<0} \atop {3x-2\geq 0}} \right.\\ \left \{ {{x-2\geq0} \atop {3x-2>(x-2)^2}} \right. " align="absmiddle" class="latex-formula">
Решим второе неравенство 2 системы:
3x-2>(x-2)²
3x-2>x²-4x+4
x²-7x+6<0<br>Нули функции:
x=6; x=1(по теореме Виета)
Решая методом интервалов получаем:
x∈(1;6)
Совокупность систем:
Совокупность:
[x∈[2/3;2)
[x∈[2;6)
Ответ: x∈[2/3;6)